The sealing behaviour of metallic O-ring - Inbar, A (Vacuum, 1971)
The behaviour of metallic O-rings used under static loads for vacuum sealing is discussed, and formulae for the leak rate vs the applied loads are derived. Thefomulae are presented in form of nomographs for easy utilization in the design of seals.